Actualization of the Maqsid Al-Shar'ah in Indonesia: A Case Study of the Spiritual Counting of Prisoners in Judicial Institutions - Aida Humaira; Imam Sujoko; Edwin Syarif; Nurul Adhha; Raju Moh Hazmi (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
Correctional institutions are undergoing a transformative shift from punitive spaces to acknowledging the humanity of inmates. This study delves into Indonesian correctional facilities' religious-based coaching programs prioritizing inmate protection, reintegration, and dignity. Analyzing these through Islamic law and Maqasid al-sharahprinciples, it explores personality development models and identifies limitations in current approaches. While initial findings showcase positive outcomes—behavioural changes and reduced distress—the study highlights the predominance of lecture-based programs, signalling the need for more comprehensive Islamic law-based models. Different inmate categories, especially those in serious crimes, display varying spiritual indicator weights. Spiritual development correlates positively with behavioural adjustments. Overcapacity issues in certain facilities, like Salemba and Jakarta Women's Correctional Institutions, pose severe challenges—from limited resources to inadequate staff ratios and hindrances in providing proper medical and psychological support, notably impacting drug abuse victims. The study underscores the urgency of restorative justice in sentencing, emphasizing rehabilitation and societal reintegration.